Identification, Molecular Cloning, and Functional Characterization of a Coniferyl Alcohol Acyltransferase Involved in the Biosynthesis of Dibenzocyclooctadiene Lignans in Schisandra chinensis - Qiang, Ting-Yan; Liu, Jiu-Shi; Dong, Yu-Qing; Mu, Xin-Lu; Chen, Yu; Luo, Hong-Mei; Zhang, Ben-Gang; Liu, Hai-Tao (Frontiers in Plant Science, 2022)
Schisandra chinensis owes its therapeutic efficacy to the dibenzocyclooctadiene lignans, which are limited to the Schisandraceae family and whose biosynthetic pathway has not been elucidated. Coniferyl alcohol is the synthetic precursor of various types of lignans and can be acetylated to form coniferyl acetate by coniferyl alcohol acyltransferase (CFAT), which belongs to the BAHD acyltransferase family. This catalytic reaction is important because it is the first committed step of the hypothetical biosynthetic pathway in which coniferyl alcohol gives rise to dibenzocyclooctadiene lignans. However, the gene encoding CFAT in S. chinensis has not been identified. In this study, firstly we identified 37 ScBAHD genes from the transcriptome datasets of S. chinensis. According to bioinformatics, phylogenetic, and expression profile analyses, 1 BAHD gene, named ScBAHD1, was cloned from S. chinensis. The heterologous expression in Escherichia coli and in vitro activity assays revealed that the recombinant enzyme of ScBAHD1 exhibits acetyltransferase activity with coniferyl alcohol and some other alcohol substrates by using acetyl-CoA as the acetyl donor, which indicates ScBAHD1 functions as ScCFAT. Subcellular localization analysis showed that ScCFAT is mainly located in the cytoplasm. In addition, we generated a three-dimensional (3D) structure of ScCFAT by homology modeling and explored the conformational interaction between protein and ligands by molecular docking simulations. Overall, this study identified the first enzyme with catalytic activity from the Schisandraceae family and laid foundations for future investigations to complete the biosynthetic pathway of dibenzocyclooctadiene lignans.